The COVID-19 Pandemic and Posttraumatic Stress Disorder: Emotional Impact on Healthcare Professions - De Pasquale, Concetta; Conti, Daniela; Dinaro, Carmela; D'Antoni, Rosa Alessia; La Delfa, Elena; Di Nuovo, Santo (Frontiers in Psychiatry, 2022)
The COVID-19 pandemic, which began in March 2020, has resulted in the deaths of hundreds of thousands of people around the world in just a few months, putting at great risk the commitment of healthcare workers unprepared to manage a worldwide phenomenon at great risk. In the early stages especially, medical staff had to deal with the pandemic at the expense of their physical and mental health, putting them particularly at risk for experiencing Post-Traumatic Stress Disorder (PTSD). The study aims to analyze the psychopathological aspects associated with PTSD, focusing on the emotional impact caused by the COVID-19 pandemic on Healthcare professionals compared with a control group. The sample analyzed over two months, from March to May 2021, included 214 participants into two groups, i.e., Healthcare professionals (N=107) and a control group (N=107). The online assessment instrument used consisted of an anonymous questionnaire, assembled ad hoc with demographic information and different standardized assessment scales (e.g. Fear of COVID-19 Scale, Profile of Mood States, and Maslach Burnout Inventory-Human Services Survey), while a further section of the survey used the DSM-5 criteria to investigate Post-Traumatic Stress Disorder (e.g. COVID-19-PTSD). The results reported that Healthcare professionals had a consistent perception of stress (mean=26.18, SD=14.60), but not at a level significantly higher than other categories of workers (mean=25.75, SD=14.65; t=0.20, p=0.84). However, they showed less emotional disturbance than the control sample, a better anxiety management skills, and a lower levels of depressive disorder and mental confusion. Specifically, the Healthcare professionals showed a condition of emotional exhaustion (T=0.64; D=0.74; A=0.62; S=0.75; C=0.64) and depersonalization (T=0.41; D=0.52; A=0.49; S=0.60; C=0.40), which is common in the burn out syndrome. In conclusion, the results obtained are useful for understanding the determinants of the emotional involvement of healthcare professions and the risk of burnout syndrome, and therefore for planning activities and support paths for these workers who are particularly at risk during prolonged and pervasive crises such as the pandemic.